Efficiency enhancement in organic solar cells by incorporating silica-coated gold nanorods at the buffer/active interface. Issue 38 (4th September 2015) - Cui, Yanxia; Zhao, Haoyang; Yang, Fan; Tong, Peiqian; Hao, Yuying; Sun, Qinjun; Shi, Fang; Zhan, Qiuqiang; Wang, Hua; Zhu, Furong
Abstract : The performance of organic solar cells can be greatly improved by incorporating silica-coated gold nanorods at the buffer/active interface. Abstract : The performance of organic solar cells (OSCs) can be greatly improved by incorporating silica-coated gold nanorods (Au@SiO2 NRs) at the interface between the hole transporting layer and the active layer due to the plasmonic effect. The silica shell impedes the aggregation effect of the Au NRs in ethanol solution which otherwise would lead to a serious reduction in the open circuit voltage when incorporating the Au NRs at the buffer/active interface. As a result, while a high open circuit voltage is demonstrated, the optimized plasmonic OSCs possess an increased short circuit current, and correspondingly an elevated power conversion efficiency with an enhancement factor of ∼11%. The origin of performance improvement in OSCs with the Au@SiO2 NRs was analyzed systematically using morphological, electrical and optical characterization methods along with theoretical simulation. It is found that the broadband enhancement in absorption, which yields a broadband enhancement in exciton generation in the active layer, is the major factor contributing to the increase in the short circuit current density. Simulation results suggest that the excitation of the transverse and longitudinal surface plasmon resonances of individual NRs as well as their mutual coupling can generate a strong electric field near the vicinity of the NRs, thereby leading to an improved exciton generation profile in the active layer. The incorporation of Au@SiO2 NRs at the buffer/active interface also improves hole extraction in the OSCs, resulting in an increase in the open circuit voltage along with a decrease in the series resistance.